2016
DOI: 10.1186/s12879-016-1783-9
|View full text |Cite|
|
Sign up to set email alerts
|

Hospitalization costs for community-acquired pneumonia in Dutch elderly: an observational study

Abstract: BackgroundCommunity-acquired pneumonia (CAP) is one of the most common infections, especially in the elderly (≥65 years). The aim of this study was to quantify hospitalization costs for CAP in different age groups and in patients with different CAP risk profiles. Secondary objectives were to assess disease severity differences between placebo and vaccine receiving participants and identify cost driving factors of CAP in hospitalized elderly in the Netherlands.MethodsThis prospective cohort study of hospitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
2
17
1
2
Order By: Relevance
“…The dataset consisted of age, gender, comorbidities (for details see supplemental file Table S1), influenza virus type (A/B), length of hospital stay (LOS) in days, intensive care unit (ICU) admission (yes/no, and length of ICU stay in days), droplet and contact isolation (yes/no), antibiotic therapy (yes/no), oseltamivir treatment (yes/no), and in-hospital mortality (yes/no, date) ( Table 1). Patients were stratified by age into four categories (18-44, 45-64, 65-74 and ≥ 75 years) and by risk of severe or complicated influenza illness into three groups (low, medium and high risk), based on the presence of comorbidities [10,20,21] (supplemental file Table S1). It was not feasible to collect data on influenza vaccination status, because it is not routinely documented in electronic patient records and a national influenza vaccination registry is not in place in The Netherlands.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dataset consisted of age, gender, comorbidities (for details see supplemental file Table S1), influenza virus type (A/B), length of hospital stay (LOS) in days, intensive care unit (ICU) admission (yes/no, and length of ICU stay in days), droplet and contact isolation (yes/no), antibiotic therapy (yes/no), oseltamivir treatment (yes/no), and in-hospital mortality (yes/no, date) ( Table 1). Patients were stratified by age into four categories (18-44, 45-64, 65-74 and ≥ 75 years) and by risk of severe or complicated influenza illness into three groups (low, medium and high risk), based on the presence of comorbidities [10,20,21] (supplemental file Table S1). It was not feasible to collect data on influenza vaccination status, because it is not routinely documented in electronic patient records and a national influenza vaccination registry is not in place in The Netherlands.…”
Section: Data Collectionmentioning
confidence: 99%
“…Differences in case definition and study population are illustrated by Dutch studies, which focused mainly on community-acquired pneumonia (CAP) [9,10,45] and invasive pneumococcal disease [10] in, respectively, an adult [9,45] and elderly population [10]. Vissink et al [10] reported that mean hospitalization costs of an elderly CAP patient amounted to €8081. In comparison, we found arithmetic mean influenza-related hospitalization costs of €6183 (95% CI €4937-€7625) in the same age group.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our discussion [1] we erroneously misclassified the study of Spoorenberg et al [2] as being a retrospective study using ICD records. Readers should know that the study of Spoorenberg et al [2] is similar to our study, a prospective cohort with confirmed CAP based on standardized diagnostic criteria.…”
Section: Erratummentioning
confidence: 99%
“…(9) Hospitalizations of patients aged over 50 years have a greater economic impact, compared with hospitalizations of individuals aged 18 years or younger (average cost per episode of EUR 5,000 vs. EUR 2,750, respectively). (10,11) These rates of mortality and costs are higher in developing countries, and published data on PP in adults and its impact on health systems in these contexts are scarce. (11) The present study adds to the literature on the in-hospital mortality from PP and related direct and indirect costs, comparing elderly and younger adult patients in a university hospital in Brazil.…”
Section: Introductionmentioning
confidence: 99%